World Single Age Records in Running From 5 km to Marathon - Knechtle, Beat; Nikolaidis, Pantelis T.; Di Gangi, Stefania (Frontiers in Psychology, 2018)
This study investigated the relationship between race times and age, in 1-year intervals, by using the world single age records, from 5 km to marathon running (i.e. 5 km, 4 miles, 8 km, 10 km, 12 km, 15 km, 10 miles, 20 km, half-marathon, 25 km, 30 km, and marathon). For each race, a regression model was fitted. Effects of sex, alone and in interaction with age, and the effect of country of origin on performance were examined in a multi-variable model. The relationship between age and race time was modelled through a 4th order-polynomial function. Women achieved their best half-marathon and marathon race time, respectively, one year and three years earlier in life than men. On the contrary, in the other races, the best women performances were achieved later in life than men (i.e. 4 miles and 30 km: 2 years later, 8km: 3 years later, 15-20-25 km: 1 year later, 10 miles : 4 years) or at the same age (i.e. 5 km, 10 km, 12 km). Moreover, age of peak performance did not change monotonically with the distance of race. For all races, except 12 km, sex differences had an absolute maximum at old ages and a relative maximum near the age of peak performance. From 8 km onward, estimated sex differences were increasing with increasing race distance. Regarding country, runners from Canada were slower than runners from the United States of America in 5 km by 00:10:05 h:min:s (p<0.001) and in half-marathon by 00:18:43 h:min:s (p<0.01). On the contrary, in marathon, they were 00:18:43 h:min faster (p<0.05). Moreover, in 10 miles, runners from Great Britain were 00:02:53 h:min:s faster (p<0.05) than runners from the United States of America. In summary, differences seem to exist in the age of peak performance between women and men and for nearly all distances sex differences showed an absolute maximum at old ages and relative maximum near the age of peak performance. Thus, these findings highlight the need for sex-specific training programs, especially near the age of peak performance and for elder runners.